A small-molecule approach to restore female sterility phenotype targeted by a homing suppression gene drive in the fruit pest Drosophila suzukii. - Suhan Ma; Xuyang Ni; Shimin Chen; Xiaomu Qiao; Xuejiao Xu; Weizhe Chen; Jackson Champer; Jia Huang (PLoS Genetics)
CRISPR-based gene drives offer promising prospects for controlling disease-transmitting vectors and agricultural pests. A significant challenge for successful suppression-type drive is the rapid evolution of resistance alleles. One approach to mitigate the development of resistance involves targeting functionally constrained regions using multiple gRNAs. In this study, we constructed a 3-gRNA homing gene drive system targeting the recessive female fertility gene Tyrosine decarboxylase 2 (Tdc2) in Drosophila suzukii, a notorious fruit pest. Our investigation revealed only a low level of homing in the germline, but feeding octopamine restored the egg-laying defects in Tdc2 mutant females, allowing easier line maintenance than for other suppression drive targets. We tested the effectiveness of a similar system in Drosophila melanogaster and constructed additional split drive systems by introducing promoter-Cas9 transgenes to improve homing efficiency. Our findings show that genetic polymorphisms in wild populations may limit the spread of gene drive alleles, and the position effect profoundly influences Cas9 activity. Furthermore, this study highlights the potential of conditionally rescuing the female infertility caused by the gene drive, offering a valuable tool for the industrial-scale production of gene drive transgenic insects.